The political uses of expert knowledge : immigration policy and social research - Boswell, Christina (Cambridge University, 2013)
Boswell develops a compelling new theory of the role of knowledge in policy, showing how policymakers use research to establish authority in contentious and risky areas of policy. This book will make fascinating reading for those interested in the interface between policymaking, academic research and political legitimacy.